The distinct features of hidden champions in Germany: A dynamic capabilities view - Christian Rammer; Alfred Spielkamp (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Hidden Champions (HCs) are firms unknown to the wider public, but global leaders in the niche markets they serve. This paper looks at distinctive features of these firms, focusing on their dynamic capabilities. Employing a unique data base on German firms, we identify a representative sample of German HCs. Based on a matching technique, we examine differences to other firms in terms of the firms' processes, position, and path. We find that HCs' competitive strategy rests on technology leadership and customisation. HCs are more open in their knowledge management, but without compromising control over the new product development process. HCs do not invest more into innovation, but achieve higher innovation success. The higher efficiency can be linked to their superior technological capabilities and to higher investment in human capital and HR management practices that mobilise the creative potential of their employees.
Keywords: L21; L25; M10; M21; O31; O32; 330; Hidden Champions; Germany; Competitive Strategy; Knowledge Management; Innovation; Dynamic Firm Capabilities